2014
DOI: 10.1155/2014/838727
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of Left Atrial Appendage Thrombus Using Single Phase Coronary Computed Tomography as Compared to Transesophageal Echocardiography in Patients Undergoing Pulmonary Vein Isolation

Abstract: Background. Transesophageal echocardiography (TEE) is used for the evaluation of the presence of left atrial appendage (LAA) thrombus prior to pulmonary vein isolation (PVI), while coronary computed tomography angiography (CCTA) is used for anatomic mapping during PVI. Methods. We compared the diagnostic performance of single phase CCTA to TEE in excluding the presence of LAA thrombus in patients undergoing PVI in 172 subjects performed during index hospitalization. Results. The mean age was 51 ± 13 years, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…As already shown, CTA is a safe method for the exclusion of LAAT [21]. Although our study is underpowered to estimate the thromboembolic event rate with one day interruption of NOACs before PVI, we did not see any stroke event during the three month follow-up of the patients.…”
Section: Discussionmentioning
confidence: 52%
“…As already shown, CTA is a safe method for the exclusion of LAAT [21]. Although our study is underpowered to estimate the thromboembolic event rate with one day interruption of NOACs before PVI, we did not see any stroke event during the three month follow-up of the patients.…”
Section: Discussionmentioning
confidence: 52%
“…A metanalysis from Romero et al showed an overall high accuracy of CT scan compared to TEE for the detection of LA/LAA thrombus. Other metanalysis of prospective studies comparing CT with TEE have had similar results and support the use of CT to rule out LA thrombus, especially when delayed imaging, ECG gating and heart rate control are performed (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 67%
“…However, TEE is an invasive procedure that requires sedation and sometimes intubation. Therefore, other alternatives have been investigated: ICE can both rule out the presence of thrombus and guide the procedure [14,15], but at a higher cost. Despite the non-negligible economic aspect, ICE presents important advantages, allowing the direct visualization of the endocardium and locating the needle and the sheath exactly against the interatrial septum.…”
Section: Discussionmentioning
confidence: 99%